Ok, so he said I would fail if I could not prove it....
3 months later I came upwith the solution....
Where is the Flaw?
A^2 = AB
A^2 - B^2 = AB - B^2
(A+B)(A-B) = B(A-B)
A+B = B
2B = B
What I did each step: (sorry forum not conducive to spaces)
A=B - Given
A^2 = AB - Multiplicative Property of Equality (A)
A^2 - B^2 = AB - B^2 - Additive Property of Equality (-B^2)
(A+B)(A-B) = B(A-B) - Evaluation
A+B = B - Reduction
2B = B - Substitution and Addition (since first statement say a=b)
2=1 - Reduction (by B)
The "^" means to the power of.